2018
DOI: 10.1136/bmjopen-2018-021610
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for subjective cognitive decline: systematic review and meta-analysis

Abstract: ObjectivesThis review provides a broad overview of the effectiveness of interventions for subjective cognitive decline (SCD) in improving psychological well-being, metacognition and objective cognitive performance.MethodsDatabases including PubMed, Web of Science and Cochrane Systematic Reviews were searched up to August 2017 to identify randomised controlled trials evaluating interventions for SCD. Interventions were categorised as psychological, cognitive, lifestyle or pharmacological. Outcomes of interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 52 publications
(90 reference statements)
2
95
1
4
Order By: Relevance
“…CT = cognitive training; CR = cognitive rehabilitation; CS = cognitive stimulation; COT = mixed cognition-oriented treatment; OA = older adults; BPSD = behavioural and psychological symptoms of dementia reviews with low confidence ratings showed results as follows. Bhome et al (2018) found no significant effect of cognitive training for individuals with subjective cognitive complaints on metacognition, Hedges' g = 0.06 (−0.12 to 0.24). In contrast, Hudes et al (2019) investigated the effects of memory-strategy training on a number of meta-memory outcomes, showing a moderate and significant effect, Hedges' g = 0.66 (0.23 to 1.08).…”
Section: Subjective Cognitive Outcomesmentioning
confidence: 80%
See 2 more Smart Citations
“…CT = cognitive training; CR = cognitive rehabilitation; CS = cognitive stimulation; COT = mixed cognition-oriented treatment; OA = older adults; BPSD = behavioural and psychological symptoms of dementia reviews with low confidence ratings showed results as follows. Bhome et al (2018) found no significant effect of cognitive training for individuals with subjective cognitive complaints on metacognition, Hedges' g = 0.06 (−0.12 to 0.24). In contrast, Hudes et al (2019) investigated the effects of memory-strategy training on a number of meta-memory outcomes, showing a moderate and significant effect, Hedges' g = 0.66 (0.23 to 1.08).…”
Section: Subjective Cognitive Outcomesmentioning
confidence: 80%
“…Populations. Seventeen reviews reported meta-analytic results for healthy older adults (Table 1), three of which focused specifically on individuals with subjective cognitive complaints (Bhome, Berry, Huntley, & Howard, 2018;Metternich, Kosch, Kriston, Harter, & Hull, 2010;Smart et al, 2017). Four reviews focused on individuals with MCI (Chandler, Parks, Marsiske, Rotblatt, & Smith, 2016;Sherman, Mauser, Nuno, & Sherzai, 2017;Wang et al, 2014).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean effect estimate was 0.29 (0.04 to 0.54). The two most recent reviews with 'low confidence' ratings showed results as following: Bhome et al (2018) found no significant effect of CT for individuals with subjective cognitive complaints on metacognition, Hedge's g 0.06 (-0.12 to 0.24). In contrast, Hudes et al (2019) (Loetscher & Lincoln, 2013).…”
Section: Subjective Cognitive Outcomesmentioning
confidence: 98%
“…4). Four reviews evaluated the effects of CT on subjective cognitive complaints in healthy older adults, with confidence ratings in the 'low' (Bhome et al, 2018;Hudes et al, 2019) and 'critically low' (Kelly et al, 2014;Metternich et al, 2010) range. The mean effect estimate was 0.29 (0.04 to 0.54).…”
Section: Subjective Cognitive Outcomesmentioning
confidence: 99%